Early Stage of COVID-19 Spreading and Simulation Trend using The Spatiotemporal Epidemiologic Modeler (STEM), Case Study in Jakarta (Journal of Pharmaceutical Negative Results, 2022)
COVID-19 virus is transmitted from human to human through splashes of saliva when the sufferer coughs, sneezes, or talks and is inhaled by the people around him. The spread of this virus started from the Chinese city of Wuhan in December 2019 which quickly spread to cities outside Wuhan including Jakarta, Indonesia. The same is in other countries, the local government in Jakarta taking some emergency decisions to minimize the virus spreading including the movement control order (MCO). This paper discusses the simulation of COVID-19 spreading in the early stage in Jakarta using a different model of disease spreading available on The Spatiotemporal Epidemiologic Modeler (STEM). The focus of this simulation is to see the effect of MCO on the COVID-19 spreading in the local area in Indonesia. The result shows that the MCO contribute to the decreasing of case number with some certain period of lag time.